Perilaku Ibu Tentang Imunisasi Dasar Pada Bayi Berusia 0-12 Bulan Di Puskesmas Glugur Kota Medan - HELMIWATI, HELMIWATI; HARTONO, ADI; SOPIANA, ANA (Journal of Engineering and Information Technology for Community Service, 2024)
The degree of child health is one of the health indicators of a nation and is usually measured through child mortality rates, immunization coverage and other parameters. Based on data from the Ministry of Health in Indonesia in 2015, the percentage of complete basic achievement in Indonesia was 86.54%. This figure has not yet reached the 2015 target of 91%, while for North Sumatra province, complete basic immunization coverage in 2015 only reached 79.9%. Behavior is a response or reaction of a person to a stimulus (stimulus from outside), perila occurs through a process of stimulus to the organism, then the organism responds "S-O-R" or stimulus organism response. Immunization is an effort to gain immunity against a disease by introducing germs that have been weakened or killed. This type of research is descriptive quantitative and this research was conducted JL.K.L Yos sudarso No.47 Kel.silasas kec. West Medan Puskesmas Glugur Medan City with the time period needed by researchers to obtain data which are mothers who have children aged 0-12 months and with a research sample of 30 people. Based on the results of the study, it was found that all respondents had positive behavior, namely 100%. After the research was conducted, it was found that the majority of respondents were aged 26-35 years and above, namely 21 people (70%), the majority of respondents' education was high school, namely 18 people (60.0%). And the majority of respondents' workers are housewives as many as 23 people (76.7%). From this study, it is expected that mothers who have babies 0-12 months should take advantage of services to complete basic immunization in children.